Design and Hardware Experiment of Concentrating Magnetic Ring of Current Sensors Used in Open-Loop Fluxgate - Yang, Wencheng; Xie, Xuegang; Yang, Qi; Huang, Jisheng (Frontiers in Energy Research, 2022)
In order to improve the ability of fluxgate current sensor to detect weak residual current, starting from the magnetic ring, which is the key magnetic concentrating element, and adopting the method of Comsol simulation analysis, the open-loop fluxgate is introduced from the aspects of magnetic ring material selection and structural design, etc. The key technology of the design of the magnetic concentrating ring of the current sensor is verified by experiments that the magnetic ring can increase the sensitivity of the current measurement by 15.4 times, and the frequency can reach 6.7 kHz, which can meet the AC and DC complex leakage current detection. Provide technical reference for designers engaged in this type of sensor.